Phosphate solubilizing Pseudomonas and Bacillus combined with rock phosphates promoting tomato growth and reducing bacterial canker disease - Bakki, Mohamed; Banane, Badra; Marhane, Omaima; Esmaeel, Qassim; Hatimi, Abdelhakim; Barka, Essaid Ait; Azim, Khalid; Bouizgarne, Brahim (Frontiers in Microbiology, 2024)
Sustainable agriculture approaches are based on the use of biofertilizers and biopesticides.Tomato (Solanum lycopersicum L.), rhizosphere could provide rhizobacteria with biofertilizing and biopesticide properties. In this work, bacteria from the rhizosphere of tomato were evaluated in vitro for plant growth promotion (PGP) properties. Five Pseudomonas isolates (PsT-04c, PsT-94s, and one Bacillus isolate (BaT-68s), with highest ability to solubilize tricalcium phosphate (TCP) and natural rock phosphate (RP) were selected for further molecular identification and characterization. Isolates showed phosphate solubilization up to 155.00 μg mL -1 .All isolates showed phosphate solubilization by organic acid production. The six isolates improved seed germination and showed an effective root colonization when tomato seeds were coated with isolates at 10 6 cfu g -1 in axenic soil conditions. Furthermore, the selected isolates were tested for beneficial effects on tomato growth and nutrient status in greenhouse experiments with or without rock phosphate (RP). Results showed that inoculated tomato plants in the presence of RP have a higher shoot and root lengths and weights compared to the control. After 60 days, significant increases in plants Ca, Na, P, protein and sugar contents were also observed in inoculated seedlings. In addition, inoculated tomato seedlings showed an increase of foliar chlorophyll a and total chlorophyll while no significant changes were observed in chlorophyll fluorescence. In greenhouse, two Pseudomonas isolates; PsT-04c and PsT-130 showed ability to trigger induced systemic resistance in inoculated tomato seedlings when subsequently challenged by Clavibacter michiganensis subsp. michiganensis, causal agent of tomato bacterial canker. High protection rate (75%) was concomitant to an increase in the resistance indicators : total soluble phenolic compounds, phenylalanine-ammonia lyase and H2O2. The results strongly demonstrated the effectiveness of phosphate solubilizing bacteria adapted to rhizosphere as biofertilizers for tomato crops and biopesticides by inducing systemic resistance to the causal agent of tomato bacterial canker disease.